The Normative Dimension of the Conception of the Individual Presented in Opinions of Judge Antonio Augusto Cançado Trindade of the ICJ – Fundamental Elements - Kozłowski, Artur (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
The subject matter of this paper is a brief presentation of the primary elements comprising the normative conception of the individual which arises out of the views expressed by Judge Antonio Augusto Cançado Trindade from the International Court of Justice. They are contained in his dissenting and individual opinions to a range of rulings handed down by the Hague-based tribunal. Their directness, clarity and judicial merit, accompanied by the rejection of the central role of the state as the primary regulator of international public law, characteristics that result from analysis of the substantive layer of his statements, can serve at the present stage of development of international law as a starting point for a range of further considerations regarding the essence of international law, its condition, and the role it can play within the international community, alongside that of the role of international justices in shaping the international legal order.
Keywords: normatywna koncepcja jednostki; Cançado Trindade, Antonio Augusto (1947-); Międzynarodowy Trybunał Sprawiedliwości; prawo międzynarodowe publiczne